2017
DOI: 10.1186/s12913-017-2025-6
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment guidelines: the association between stroke risk stratified comparing CHADS2 and CHA2DS2-VASc score levels and warfarin prescription for adult patients with atrial fibrillation

Abstract: BackgroundIschemic stroke is a risk associated with atrial fibrillation (AF) and is estimated to occur five times more often in afflicted patients than in those without AF. Anti-thrombotic therapy is recommended for the prevention of ischemic stroke. Risk stratification tools, such as the CHADS2, and more recently the CHA2DS2-VASc, for predicting stroke in patients with AF have been developed to determine the level of stroke risk and assist clinicians in the selection of antithrombotic therapy. Warfarin, for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Patients were prescribed anticoagulants according to guidelines, warfarin or a non-vitamin K antagonist oral anticoagulant based on CHA2DS2-Vasc scores. 31,32 When discharged from hospital, AF patients were encouraged to reduce the risk of new AF episodes by exercising regularly, refraining from smoking or using snuff, not exceeding a moderate intake of alcohol and coffee, and avoiding psychological distress, in accordance with provided guidelines. 33 If the AF episodes occurred occasionally, without body-mind impact, no measures were needed; but if the AF episodes became more frequent or produced symptoms, such as shortness of breath and chest pain, they were advised to contact healthcare.…”
Section: Interventionsmentioning
confidence: 99%
“…Patients were prescribed anticoagulants according to guidelines, warfarin or a non-vitamin K antagonist oral anticoagulant based on CHA2DS2-Vasc scores. 31,32 When discharged from hospital, AF patients were encouraged to reduce the risk of new AF episodes by exercising regularly, refraining from smoking or using snuff, not exceeding a moderate intake of alcohol and coffee, and avoiding psychological distress, in accordance with provided guidelines. 33 If the AF episodes occurred occasionally, without body-mind impact, no measures were needed; but if the AF episodes became more frequent or produced symptoms, such as shortness of breath and chest pain, they were advised to contact healthcare.…”
Section: Interventionsmentioning
confidence: 99%
“…A report from the PINNACLE registry concluded that a collaborative care model, using both physicians and nurses, may provide an overall comparable quality of outpatient cardiovascular care compared with a physician‐only model 50 . However, there is available evidence showing that a multi‐disciplinary healthcare team constituted of primary care providers (physicians [including cardiologists, arrhythmologists, general practitioners and other specialists], physician assistants and nurse practitioners), nurses and pharmacists can provide improved medical management for stroke prevention in AF patients 51 . Furthermore, a structured AF management within an integrated care approach should include some core components such as: (a) patient‐centeredness; (b) multidisciplinary team; (c) use of smart technology; and (d) application of a comprehensive approach to care with access to all treatment options 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, CHADS 2 /CHA 2 DS 2 VAS C scoring system was frequently used to guide toward oral anticoagulation therapy. As recommended by several guidelines, patients who had CHADS 2 /CHA 2 DS 2 VAS C ≧2 should initiate warfarin treatment (Kim et al, 2016 ; Chapman et al, 2017 ). However, among 12 included studies in our meta-analysis, which mainly enrolled patients who had CHADS 2 /CHA 2 DS 2 VAS C ≧2, there was not a consistent conclusion about the risk-benefit profile of warfarin in these patients (Chan et al, 2009 , 2015 ; Winkelmayer et al, 2011 ; Wakasugi et al, 2013 ; Genovesi et al, 2015 ; Shen et al, 2015 ; Yodogawa et al, 2015 ; Garg et al, 2016 ; Mitsuma et al, 2016 ; Yamashita et al, 2016 ; Kai et al, 2017 ; Yoon et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%